Participatory Indicators of Success of Community Forestry Programs in Uganda - Buyinza Mukadasi (Jurnal Ilmu Kehutanan, 2008)
In Uganda, a large diversity of community initiated forest management systems have evolved recently in response to severe degradation of forests and grazing land and biomass shortages. Forestry professional, forest user group and farmers were organized in June 2004 to develop commonly agreed indicators of the performance of Community Forestry Program in Uganda. Indicators, such as access to fuel wood, incidence of forest fire and amount of community funds raised through the sale offorest products are commonly agreed at local level. Women participation in forestry related meetings and taste of drinking water in the watershed area are also important. Equitable benefit sharing by the community forest users serves as an indicator of better access to forest products. Socio-economic changes such as women participation in forest related decision-making, income generated from community forests, and equity of benefits from community forests also, reflect the program success.